Diseño e implementación de un modelo administrativo para las oficinas Riobamba y Ambato, de la empresa punto net s.a. y su incidencia en los niveles de desempeño. Período marzo-diciembre 2013 - Velasteguí Salazar, Lupe Elizabeth (2015)
This study was aimed to develop and implement an Administrative Model for Punto Net S.A. Riobamba and Ambato branch offices and its impact on performance levels. March - December 2013 period. The research developed was based on determining the key elements supported by the phases of the administrative process which allowed the design of an Administrative Management tool for Punto Net according to the needs required to improve its development and growth in the technology world and the benefit of adopting it favorably. The model suggested in order to meet the organizational objectives is to evaluate the performance of the employees and specifically to do it under the competence approach. Therefore, an administrative model for the development of competencies was carried out, it helps as a support for the decisions about selection, recruitment and career plans within the Punto Net, Ambato and Riobamba branch offices. Some surveys were used in the analysis of results, they were applied to all the technical and commercial staff in both branches, and two questionnaires for performance evaluation were developed according to the competencies defined for each group. Evaluations were made through the forms set out in the Manual of Performance Evaluation, aimed to the employees of Riobamba and Ambato branches in order to establish the relevance of the proposal. These results will implement training plans and will be aimed to the appropriate results for the company. The demonstration of the hypothesis concluded that it is necessary to implement administrative management tools which will improve the efficiency of employees through an organizational diagnosis which is very important for improving the performance of the job since it allows getting important information for improving processes, functions and performance.